Effect of plant spacing on the yield of the yellow passion fruit at Viamão, RS, Brazil - Ritzinger, Rogério; Manica, Ivo; Riboldi, João (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was stablished at Viamão, RS, Brazil, with the objective of determining the effect of six planting distances on the number and weight of fruit per plant and per hectare and also on the average weight of the fruit of the yellow passion fruit (Passiflora edulis f. flavicarpa Deg.). The spaces in the rows were 2,00, 2,75, 3,50, 4,25, 5,00 and 5,75 m and 2,50 m between rows, corresponding to densities ranging from 695 to 2000 plants/ha. The harvesting season began in January and extended until September during 1981 and 1982, with two distinct peaks of production. For the two harvests, the effect of spacing on fruit weight per plant was quadratic and on fruit number was linear, with the tendency of having the maximum responses at 2,50 x 5,00 m spacing. The weight and number of fruits per hectare decreased linearly with the spacing in the row, having the maximum value at 2,50 x 2,00 m spacing. The spacings of 2,50 , x 3,50 m and 2,50 x 4,25 m are suggested as the most adequate for this crop because they represent the balancing point between production per plant and per hectare. The spacing did not affect the average weight of the fruit in both harvests.
Keywords: Passiflora edulis f. flavicarpa; planting distances; harvest; quadratic and linear responses